Qualitative Analysis of Community Digital Literacy in Overcoming Hoaxes - Rifaany Camelia Azkia; Raudatul Ismi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This research analyzes the role of digital literacy in dealing with the spread of hoaxes among women aged 40 years and over in Bintaro Jaya Village, Ampenan District. With the rapid development of technology, access to information is getting easier, but it also increases the risk of spreading hoaxes. The research used a descriptive qualitative approach with 55 female respondents who were active on social media. Data was collected through structured interviews and analyzed qualitatively. The research results show that although respondents have good access to technology, most have difficulty evaluating and filtering information. The majority use cellphones to access information, but only 50% actively select information based on the credibility of the source. These findings highlight the need to increase digital literacy to empower women aged 40 years and over to face hoaxes in the digital era.